TINGKAT PENGETAHUAN IBU HAMIL TENTANG EFEK RADIASI SINAR-X DI BIDANG KEDOKTERAN GIGI PADA SAAT KEHAMILAN (STUDI DILAKUKAN DI PRAKTEK BIDAN SWASTA DESA SUKA DAMAI KECAMATAN LUENG BATA BANDA ACEH) - Kemala Hayati; Cut Fera Novita; Rizki Zuliati (Dentistry Faculty, 2018)
X-rays radiation is an electromagnetic wave that can pass through space and disperse the energy. One of utilization of X-rays radiation in dentistry is diagnostic procedures. In addition, X-rays radiation can also cause some risks, such as cell, tissue, and organ damage. These risks can damage to operators and patients, including pregnant woman who are having treatment using X-rays radiation. The risks of X-rays radiation to pregnant woman can be caused by the lack of knowledge about radiation risk. This research aims to observe the knowledge level of pregnant woman about X-rays radiation effects in dentistry during pregnancy in private midwifery practice Desa Suka Damai Kecamatan Lueng Bata Banda Aceh. The type of this study was descriptive. The subjects were chosen with purposive sampling method obtained to match the inclusion on criteria. Collecting data was done by using questionnaire and distributed to subject who have given the informed concent. The result of this research showed that knowledge level of 30 subjects pregnant woman about X-rays radiation effects in dentistry during pregnancy in private midwifery practice Desa Suka Damai Kecamatan Lueng Bata Banda Aceh which has good category was 20%, fair 36,7%, poor 16,7%, and very poor 26,7%, so it can be concluded that knowledge level of these pregnant woman are dominantly fair.Keywords : X-Rays Radiation in Dentistry, Pregnant Woman, Knowledge.